Drought stress alleviation in rice by endophytic Trichoderma sp. via modulation of physiological and antioxidant responses - Abhishek R. R.; Kumaraswamy H. M. (The Bioscan, 2026)
Drought is a major constraint to rice production, and beneficial endophytic fungi offer a promising strategy to enhance plant resilience under water-limited conditions. In this study, a drought-tolerant fungal endophytic Trichoderma sp. was evaluated for its ability to improve the physiological and biochemical performance of rice (Oryza sativa L. cv. IR-64) under greenhouse-imposed drought stress. Plants were grown under four treatment combinations with and without endophyte inoculation and drought. Endophyte-treated plants showed improved growth under optimal conditions and exhibited strong protection against drought-induced declines in chlorophyll content, SPAD index, and leaf water status. Enhanced soluble sugar accumulation and elevated antioxidant enzyme activities further indicated improved osmotic balance and strengthened defense responses in inoculated plants exposed to drought. Overall, the Trichoderma sp. strain substantially mitigated drought-induced damage by enhancing water retention, maintaining photosynthetic capacity, and activating antioxidant and osmoprotective mechanisms. These findings highlight the potential of endophytic fungi as effective biological tools for improving drought tolerance in rice. Keywords Trichoderma sp., Rice IR-64, Drought stress, Endophytic fungi.